2019
DOI: 10.1017/s1368980019002970
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and hearing loss among middle–older aged adults in the USA: findings from National Health and Nutrition Examination Survey

Abstract: Objective:To examine the associations between overall diet quality and hearing function among middle–older aged adults in the USA.Design:Cross-sectional analysis. Diet quality was examined using the Mediterranean Diet Score (MDS), using data from a single 24 h dietary recall. Hearing function was objectively measured by audiometry assessments and hearing loss, including high- and low-frequency hearing loss, was defined as pure-tone averages at specific ranges of hearing frequencies >25 dB. Weighted logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…[30][31][32][33][34] Compared to single nutrient analysis, dietary patterns account for the combined effect of various foods and may have a stronger association with disease risk than for individual components. 35,36 Prior studies have examined the relationship between dietary patterns and HL, 13,37,38 however, these dietary patterns were not designed to explore the inflammatory potential of diets. Moreover, the results of previous studies for the relationship between inflammatory food consumption and hearing loss are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34] Compared to single nutrient analysis, dietary patterns account for the combined effect of various foods and may have a stronger association with disease risk than for individual components. 35,36 Prior studies have examined the relationship between dietary patterns and HL, 13,37,38 however, these dietary patterns were not designed to explore the inflammatory potential of diets. Moreover, the results of previous studies for the relationship between inflammatory food consumption and hearing loss are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Although, they conjectured that there was a nonlinear association between the inflammatory potential of the diet and subjective hearing loss, they did not further explore the nonlinear association. Interestingly, Huang et al 38 also found that higher adherence to a Mediterranean-style diet, which is considered as an anti-inflammatory diet, was positively associated with low-frequency hearing loss among middle–older aged male adults in the USA. These results may imply inflammation plays a dual role in the risk of hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural hearing loss has been linked to cholesterol dysregulation including in hypercholesterolaemia and trafficking disorders such as Niemann-Pick type C disease (Malgrange et al., 2015). There is also some evidence that diet can affect severity of hearing loss (Rosen et al., 1970; Yamasoba et al., 2013; Yang et al., 2015; Huang et al., 2020). Reducing cholesterol levels through diet and drug interventions may therefore be beneficial for reducing severity of ORP2-mediated hearing loss in patients.…”
Section: Oxysterol Binding Protein-related Protein 2 (Orp2)mentioning
confidence: 99%
“…It is imperative that risk factor control is the foundation for limiting the number of people who develop hearing loss. Multiple risk factors, including metabolic syndrome components 3 and lifestyle habits of individuals, such as smoking 4 and dietary habits, 5 may give rise to hearing loss. Some researchers have demonstrated that cardiovascular disease (CVD) and risk factors for CVD are associated with hearing loss 6‐8 .…”
Section: Introductionmentioning
confidence: 99%